Beneficial effects of methanolic extract of Indigofera linnaei Ali. on the inflammatory and nociceptive responses in rodent models - Raju Senthil Kumar; Balasubramanian Rajkapoor; Perumal Perumal; Sekar Vinoth Kumar; Arunachalam Suba Geetha (Brazilian Journal of Pharmaceutical Sciences)
ABSTRACT Indigofera linnaei Ali. (Tamil Name: Cheppu Nerinjil) belongs to the family Fabaceae, used for the treatment of various ailments in the traditional system of medicine. In the present study, the beneficial effects of methanol extract of whole plant of I. linnaei (MEIL) were evaluated on inflammation and nociception responses in rodent models. In vitro nitric oxide (NO), lipoxygenase (LOX) and cyclooxygense (COX) inhibitory activities were also performed to understand the mode of action. MEIL at the dose of 200 & 400 mg/kg, p.o. significantly inhibited carrageenan induced rat paw volume and reduced the weight of granuloma in cotton pellet granuloma model. The results obtained were comparable with the standard drug aceclofenac. The anti-nociceptive effect of MEIL in mice was evaluated in hot plate and acetic acid induced writhing model. The plant extract significantly reduced the number of writhes and the analgesic effect was higher than that of the standard drug aspirin. However, the extract fails to increase the latency period in hot plate method suggesting that the extract produce nociception by peripheral activity. The extract produced inhibitory effect on NO, LOX and COX in concentration dependent manner. The extract exhibited pronounced and selective COX-2 inhibition. Altogether, these results suggested that the methanol extract of Indigofera linnaei could be considered as a potential anti-inflammatory and analgesic agent.